Report on the seismic performance of three-dimensional moment-resisting timber frames with frictional damping in beam-to-column connections. Issue 11 (August 2018) - Polocoșer, Tiberiu; Leimcke, Jonas; Kasal, Bohumil
The seismic performance of three-dimensional moment-resisting timber frames with frictional damping devices was investigated experimentally. This article describes a novel three-dimensional beam-to-column connection which was designed to behave rigidly up to moderate seismic intensities and to start the frictional dissipating behavior at higher intensities. The three-dimensional beam-to-column connection component was initially tested under cyclic loading, and then the connection was mounted in a three-level prototype frame and tested on a shake table. From the cyclic loading tests, the energy dissipation of the proposed beam-to-column connection was higher than the equivalent rigid connection. The frame demonstrated self-aligning capabilities without permanent drift at seismic intensities up to 1.4  g and maintained strength up to high seismic intensities of 2  g . Because wood frames allow for large elastic deflections and can exhibit excellent self-aligning capabilities ( i.e ., connections tolerate large rotations within safe stress levels), the proposed frictional beam-to-column connection is a promising alternative for moment-resisting timber frames that can be used to prevent structural members from reaching critical stresses.